Question
upstudy study bank question image url

A graphing calculator is recommended. Let \( f(x)=3 e^{x} \cos (x) \) (a) Find \( f^{\prime}(x) \) and \( f^{\prime \prime}(x) \)

Ask by Parry Cox. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

First derivative \( f'(x) = 3 e^{x} (\cos(x) - \sin(x)) \). Second derivative \( f''(x) = -6 e^{x} \sin(x) \).

Solution

To find the first and second derivatives of the function \( f(x) = 3 e^{x} \cos(x) \), we'll use the product rule and the chain rule from calculus. ### (a) First Derivative \( f'(x) \) **Function:** \[ f(x) = 3 e^{x} \cos(x) \] **Applying the Product Rule:** \[ f'(x) = 3 \left( \frac{d}{dx} \left( e^{x} \cos(x) \right) \right) \] \[ f'(x) = 3 \left( e^{x} \cos(x) + e^{x} (-\sin(x)) \right) \] \[ f'(x) = 3 e^{x} (\cos(x) - \sin(x)) \] **Simplified First Derivative:** \[ f'(x) = 3 e^{x} (\cos(x) - \sin(x)) \] ### Second Derivative \( f''(x) \) **First Derivative:** \[ f'(x) = 3 e^{x} (\cos(x) - \sin(x)) \] **Applying the Product Rule Again:** \[ f''(x) = 3 \left( \frac{d}{dx} \left( e^{x} (\cos(x) - \sin(x)) \right) \right) \] \[ f''(x) = 3 \left( e^{x} (\cos(x) - \sin(x)) + e^{x} (-\sin(x) - \cos(x)) \right) \] \[ f''(x) = 3 e^{x} (\cos(x) - \sin(x) - \sin(x) - \cos(x)) \] \[ f''(x) = 3 e^{x} (-2 \sin(x)) \] \[ f''(x) = -6 e^{x} \sin(x) \] **Simplified Second Derivative:** \[ f''(x) = -6 e^{x} \sin(x) \] ### Summary - **First Derivative:** \[ f'(x) = 3 e^{x} (\cos(x) - \sin(x)) \] - **Second Derivative:** \[ f''(x) = -6 e^{x} \sin(x) \] These derivatives can be used for further analysis, such as finding critical points, concavity, and points of inflection for the function \( f(x) \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the first and second derivatives of \( f(x) = 3 e^{x} \cos(x) \), we can use the product rule and the chain rule. 1. **First Derivative \( f^{\prime}(x) \)**: Let \( u(x) = 3 e^x \) and \( v(x) = \cos(x) \). Then \( u'(x) = 3 e^x \) and \( v'(x) = -\sin(x) \). According to the product rule, \( f^{\prime}(x) = u' v + u v' \): \[ f^{\prime}(x) = (3 e^x)(\cos x) + (3 e^x)(-\sin x) = 3 e^x (\cos x - \sin x) \] 2. **Second Derivative \( f^{\prime \prime}(x) \)**: Now, we differentiate the first derivative. Using the product rule again: Let \( A(x) = 3 e^x \) and \( B(x) = \cos x - \sin x \). Then \( A'(x) = 3 e^x \) and \( B'(x) = -\sin x - \cos x \). Now, applying the product rule: \[ f^{\prime \prime}(x) = A'B + AB' = (3 e^x)(\cos x - \sin x) + (3 e^x)(-\sin x - \cos x) = 3 e^x[( \cos x - \sin x) + (-\sin x - \cos x)] = 3 e^x(-2\sin x) \] Thus, the first derivative is: \[ f^{\prime}(x) = 3 e^x (\cos x - \sin x) \] and the second derivative is: \[ f^{\prime \prime}(x) = -6 e^x \sin x \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy